Characterizing U.S. drought over the past 20 years using the U.S. drought monitor. (25th April 2022) - Leeper, Ronald D.; Bilotta, Rocky; Petersen, Bryan; Stiles, Crystal J.; Heim, Richard; Fuchs, Brian; Prat, Olivier P.; Palecki, Michael; Ansari, Steve
Abstract: The main challenge of evaluating droughts in the context of climate change and linking these droughts to adverse societal outcomes is a lack of a uniform definition that identifies drought conditions at a location and time. The U.S. Drought Monitor (USDM), created in 1999, is a well‐established composite index that combines drought indicators across the hydrological cycle (i.e., meteorological to hydrological) with information from local experts. This makes the USDM one of the most holistic measures for evaluating past drought conditions across the United States. In this study, the USDM was used to define drought events as consecutive periods in time where the USDM status met or exceeded D1 conditions over the past 20 years. This analysis was applied to 5 km grid cells covering the U.S. and Puerto Rico to characterize the frequency, duration, and intensification rates of drought, and the timing of onset, amelioration, and other measures for every drought event on record. Results from this analysis revealed stark contrasts in the evolution of drought across the United States. Over the western United States, droughts evolved much slower, resulting in longer‐lasting but fewer droughts. The eastern United States experienced more frequent, shorter‐duration events. Given the slower evolution from onset to drought peak, flash droughts, which made up 9.8% of all droughts, were less common across the western United States, with a greater frequency over the southern United States. The most severe drought event on record was the 2012 drought, when more than 21% of the United States experienced its largest number of weeks at or above extreme (D3) drought conditions. The availability of historical drought events would support future societal impacts studies relating drought to adverse outcomes and aid in the evaluation of mitigation strategies by providing a dataset to local decision makers to compare and evaluate past droughts. Abstract : A well‐established measure of drought was used to identify historical drought events across the U.S. and Puerto Rico. This study revealed important contrasts in drought evolution between the Western and Eastern regions of the U.S. and northern and southern portions of Alaska. It is believed that a dataset of historical drought events that documents the timing of onset and intensification rates among other measures for each event will aid future drought impact studies and evaluations of mitigation strategies.